Current Status and Future Perspectives of Immunotherapies in Bladder Cancer - Gökhan Çolak; Bilgin Demir (Acta Haematologica Oncologica Turcica)
Bladder cancer exhibits a broad spectrum of progression, ranging from early stage to metastatic disease. Approximately 75% of newly diagnosed patients present with non-muscle-invasive bladder cancer, while the remaining 25% have muscle-invasive bladder cancer or metastatic disease. The prognosis of advanced urothelial carcinoma is poor, with more than 90% of patients succumbing to metastatic disease within five years of diagnosis. In recent years, the role of immunotherapies, particularly immune checkpoint inhibitors, in the treatment of bladder cancer has become increasingly recognized. This review aims to evaluate the current status of immunotherapies in bladder cancer and their future potential.